Glycated ACE2 reduces anti-remodeling effects of renin-angiotensin system inhibition in human diabetic hearts - Raffaele Marfella; Nunzia D’Onofrio; Gelsomina Mansueto; Vincenzo Grimaldi; Maria Consiglia Trotta; Celestino Sardu; Ferdinando Carlo Sasso; Lucia Scisciola; Cristiano Amarelli; Salvatore Esposito; Michele D’Amico; Paolo Golino; et al. (Cardiovascular Diabetology, 2022)
Abstract Background High glycated-hemoglobin (HbA1c) levels correlated with an elevated risk of adverse cardiovascular outcomes despite renin-angiotensin system (RAS) inhibition in type-2 diabetic (T2DM) patients with reduced ejection fraction. Using the routine biopsies of non-T2DM heart transplanted (HTX) in T2DM recipients, we evaluated whether the diabetic milieu modulates glycosylated ACE2 (GlycACE2) levels in cardiomyocytes, known to be affected by non-enzymatic glycosylation, and the relationship with glycemic control. Objectives We investigated the possible effects of GlycACE2 on the anti-remodeling pathways of the RAS inhibitors by evaluating the levels of Angiotensin (Ang) 1–9, Ang 1–7, and Mas receptor (MasR), Nuclear-factor of activated T-cells (NFAT), and fibrosis in human hearts. Methods We evaluated 197 first HTX recipients (107 non-T2DM, 90 T2DM). All patients were treated with angiotensin-converting enzyme inhibitor (ACE-I) or angiotensin receptor blocker (ARB) at hospital discharge. Patients underwent clinical evaluation (metabolic status, echocardiography, coronary CT-angiography, and endomyocardial biopsies). Biopsies were used to evaluate ACE2, GlycACE2, Ang 1–9, Ang 1–7, MasR, NAFT, and fibrosis. Results GlycACE2 was higher in T2DM compared tonon-T2DM cardiomyocytes. Moreover, reduced expressions of Ang 1–9, Ang 1–7, and MasR were observed, suggesting impaired effects of RAS-inhibition in diabetic hearts. Accordingly, biopsies from T2DM recipients showed higher fibrosis than those from non-T2DM recipients. Notably, the expression of GlycACE2 in heart biopsies was strongly dependent on glycemic control, as reflected by the correlation between mean plasma HbA1c, evaluated quarterly during the 12-month follow-up, and GlycACE2 expression. Conclusion Poor glycemic control, favoring GlycACE2, may attenuate the cardioprotective effects of RAS-inhibition. However, the achievement of tight glycemic control normalizes the anti-remodeling effects of RAS-inhibition. Trial registration: https://clinicaltrials.gov/ NCT03546062.